2023
DOI: 10.1111/dom.15004
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and treating the protean manifestations of diabetic autonomic neuropathy

Abstract: The manifestations of diabetic autonomic neuropathy (DAN) are protean and clinically involve multiple systems, including the cardiovascular system, the gastrointestinal system, the genitourinary system as well as the sweat glands (sudomotor dysfunction) and the gallbladder. In addition, cardiac autonomic neuropathy (CAN) is associated with a correctible inability to appreciate and correct hypoglycaemia. While not a clinical problem, pupillary involvement should be the clue and the catalyst to investigate for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“… 40 The presence of diabetic autonomic neuropathy accelerates or worsens DR, with impaired haemodynamics/autoregulation and abnormal parasympathetic/sympathetic balance due to diabetic autonomic neuropathy. 42 Previous studies have also found that the QTc interval and QRS-T angle are associated with diabetic autonomic neuropathy. 41 , 43 However, there is also evidence of autonomic dysregulation in prediabetes, especially involving the cardiovascular system.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 40 The presence of diabetic autonomic neuropathy accelerates or worsens DR, with impaired haemodynamics/autoregulation and abnormal parasympathetic/sympathetic balance due to diabetic autonomic neuropathy. 42 Previous studies have also found that the QTc interval and QRS-T angle are associated with diabetic autonomic neuropathy. 41 , 43 However, there is also evidence of autonomic dysregulation in prediabetes, especially involving the cardiovascular system.…”
Section: Discussionmentioning
confidence: 95%
“… 44 Loss of the parasympathetic vagus nerve leads to sympathetic overactivity which, in turn, may lead to arrhythmias by prolonging the QT interval. 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, anesthesia develops seemingly paradoxically alongside neuropathic pain (anesthesia dolorosa) and impairs not only superficial sensory modalities (pain and temperature sensation) but also deeper ones, including proprioception, leading to gait unsteadiness. In severe cases, a generalized autonomic neuropathy develops, leading to urinary urgency, bowel hypomotility, erectile dysfunction, impaired cardiovagal reflexes (leading to orthostatic intolerance), and, in the most extreme cases, impaired pupillary responses 73 …”
Section: Diabetesmentioning
confidence: 99%
“…In 2013, 8.3% of people were affected with diabetes worldwide (International Diabetes Federation, 2013). T2DM has a long asymptomatic pre-clinical phase during which time, 20-30% of patients develop complications such as retinopathy, cardiovascular disease, neuropathy, and nephropathy (Sinnott et al, 2015;Bell, 2023). Therefore, early detection followed by lifestyle modification and/or pharmacotherapy can delay or arrest disease progression (Knowler, 2002; American diabetes association, 2009).…”
Section: Introductionmentioning
confidence: 99%